2020
DOI: 10.2174/1874205x02014010006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Vitamin A and D Levels in Acute Phase Ischemic Stroke and Clinical Outcome

Abstract: Background: In the last decade, a number of studies have examined the relationship between serum vitamin D concentration and the risk of cerebrovascular events. Besides vitamin D, the latest evidence shows that vitamin A is also a risk factor for cerebrovascular disease. Vitamin A and its derivatives act biologically via specific nuclear receptors that regulate gene transcription. Vitamin A receptors can also interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
1
6
0
8
Order By: Relevance
“…Overall, five studies showed an improvement in stroke impairment. Kadri et al 18 and Hesami et al 24 both found improvements on the National Institute of Health Stroke Scale in the vitamin D supplementation group. Narasimhan et al 20 and Acharya et al 23 used the Scandinavian Stroke Scale, and while Narasimhan et al 20 noted statistical improvement, in the study by Acharya et al 23 an improvement was suggested, however only within group comparisons were reported (mean improvement in scores 12.59 in vitamin D group vs 3.25 in control group), with no standard deviations so between group differences could not be calculated.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Overall, five studies showed an improvement in stroke impairment. Kadri et al 18 and Hesami et al 24 both found improvements on the National Institute of Health Stroke Scale in the vitamin D supplementation group. Narasimhan et al 20 and Acharya et al 23 used the Scandinavian Stroke Scale, and while Narasimhan et al 20 noted statistical improvement, in the study by Acharya et al 23 an improvement was suggested, however only within group comparisons were reported (mean improvement in scores 12.59 in vitamin D group vs 3.25 in control group), with no standard deviations so between group differences could not be calculated.…”
Section: Resultsmentioning
confidence: 97%
“…A total of 43 articles underwent full text review of which 33 studies were subsequently excluded (Figure 1 and Appendix B for list of excluded studies at full text stage). Ten studies were included in this systematic review, including eight randomized controlled trials 7,[18][19][20][21][22][23][24] and two non-randomized studies of intervention, 3,25 examining a total of 691 patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pada studi ini, didapatkan bahwa 7 artikel studi yang digunakan dalam evidence based case study ini menggunakan desain uji terkontrol acak atau randomized controlled trials (RCT) (Gupta et al, 2016;Hesami et al, 2022;Kadri et al, 2020;Karasu & Karataş, 2021;Narasimhan & Balasubramanian, 2017;Rezaei et al, 2021;Torrisi et al, 2021). Usia pasien yang terlibat dalam studi penelitian yang disertakan berkisar antara 18-80 tahun.…”
Section: Results Desain Dan Karakteristik Studiunclassified